Faktor-Faktor yang Mempengaruhi Kejadian Depresi pada Remaja di Indonesia dengan Pendekatan Teori Lingkungan - Prihatmono, Ignatius Gonggo (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
Depression in adolescents is one of the serious mental health issues in Indonesia. This study aims to explore the factors that affect the incidence of depression in adolescents using an environmental theory approach. This approach explains the influence of different levels of the environment, from families to communities, to social policies, on an individual's mental health. The research method uses literature study by analyzing various secondary sources, such as scientific journals, official reports, and books, that are relevant to the research topic. Data is collected through systematic searches using related keywords in leading academic databases. The results showed that microenvironmental factors, such as family disharmony and peer pressure, as well as macro environments, such as social stigma and lack of access to mental health services, were the leading causes of depression in adolescents. This study recommends a holistic approach to dealing with depression in adolescents through increased family support, provision of counseling services in schools, and community education campaigns. With this approach, it is hoped that Indonesia's young generation can overcome mental health challenges and grow into emotionally healthy individuals.